The Meaning of Symbols in the Kalompoang Kalattuang Tradition in Paranglompoa Village, Bontolempangan District, Gowa Regency - Miftahul Jannah; Abd. Rasyid Masri; Ramsiah Tasrudddin (Jurnal Mercusuar, 2023)
This study adopts a qualitative approach to uncover the symbolic meanings, social interactions, and ecological impacts within the Kalompoang Kalattuang Tradition in Paranglompoa Village, Bontolempangan, Gowa. This approach involves exploring written or spoken word analyses from community figures and participants involved in the tradition, with a deep focus on understanding the community's culture, values, beliefs, and language. The study also utilizes the approaches of dakwah (Islamic propagation), sociology, and semiotics to delve into the dimensions of religion, society, and ecology within the interactions of the community and the implementation of the Kalompoang Kalattuang Tradition.The research findings indicate that the Kalompoang Kalattuang Tradition in Dusun Borongbulo reflects the social, religious, and ecological dynamics within the community. Socially, this tradition strengthens community bonds, values heritage, and expresses cultural identity. In terms of religion, despite the presence of elements that might be perceived as conflicting with Islamic creed, such as the reverence for ancestral spirits, the core essence of this practice is gratitude expression and unity within the faith. Ecologically, the tradition demonstrates the community's commitment to preserving and respecting nature, emphasizing environmental responsibility and sustainability. This research offers crucial insights into how the social, religious, and ecological aspects interact and manifest within the unique cultural practices.